Cataloging correctly for kids an introduction to the tools - Intner, Sheila S.; Fountain, Joanna F.; Weihs, Jean Riddle (IG library, 2011)
It is a time of productive and exciting changes in the cataloging world, and cataloging for children is placed squarely in the middle of this upheaval, offering librarians working with kids a particular opportunity. This new fifth edition of the classic Cataloging Correctly for Kids points the way towards providing effective cataloging for materials intended for children and young adults. Based on guidelines issued by the Association for Library Collections and Technical Services (ALCTS), this handbook is a one-stop resource for librarians who organize information for children. Revisions include comprehensive updates on bibliographic description and subject access, A new chapter exploring cataloging for non-English-speaking and preliterate children, Guidance on when and how to move to RDA, the next generation of cataloging guidelines, With advice contributed by experienced, practicing librarians, the fifth edition of Cataloging Correctly for Kids offers a complete overview of the best methods for enabling children to find the information they want and need.